2020
DOI: 10.3390/cancers12123570
|View full text |Cite
|
Sign up to set email alerts
|

RAC1B Regulation of TGFB1 Reveals an Unexpected Role of Autocrine TGFβ1 in the Suppression of Cell Motility

Abstract: Autocrine transforming growth factor (TGF)β has been implicated in epithelial-mesenchymal transition (EMT) and invasion of several cancers including pancreatic ductal adenocarcinoma (PDAC) as well as triple-negative breast cancer (TNBC). However, the precise mechanism and the upstream inducers or downstream effectors of endogenous TGFB1 remain poorly characterized. In both cancer types, the small GTPase RAC1B inhibits cell motility induced by recombinant human TGFβ1 via downregulation of the TGFβ type I recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…Moreover, our strong confidence in RAC1B being a tumor suppressor led us to hypothesize that its newly identified targets should themselves be anti-oncogenic. Rigorously sticking to this concept allowed us to verify a hitherto unappreciated anti-migratory function for SMAD3 [ 13 ] and autocrine TGFβ1 [ 100 ], two factors that had before been considered classical tumor promoters. Although the majority of our observations were made in selected adenocarcinoma cell lines of pancreatic and breast origin, we surmise that these mechanisms also operate in other but not necessarily all epithelial cells or cancer types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our strong confidence in RAC1B being a tumor suppressor led us to hypothesize that its newly identified targets should themselves be anti-oncogenic. Rigorously sticking to this concept allowed us to verify a hitherto unappreciated anti-migratory function for SMAD3 [ 13 ] and autocrine TGFβ1 [ 100 ], two factors that had before been considered classical tumor promoters. Although the majority of our observations were made in selected adenocarcinoma cell lines of pancreatic and breast origin, we surmise that these mechanisms also operate in other but not necessarily all epithelial cells or cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of autocrine TGFβ1 to induce SMAD3 protein expression, together with the finding that non-C-terminally phosphorylated SMAD3 can inhibit invasion (see above) led us to propose that the endogenous TGFB1 gene is involved in mediating the anti-EMT and anti-migratory effect of RAC1B. Intriguingly, knock-down of TGFB1 or antibody-mediated neutralization of autocrine TGFβ1 in the culture supernatant enhanced rather than decreased both the expression of SNAI1 or SNAI2 and the cells’ migratory activity [ 100 ]. Since RAC1B, autocrine TGFβ1, and SMAD3 all inhibited migration, and co-depletion of either RAC1B and TGFB1 or RAC1B and SMAD3 failed to provide an additional or synergistic effect over those with depletion of only one gene, we proposed the RAC1B-autocrine TGFβ-SMAD3 axis to represent a novel tumor suppressor pathway [ 100 ].…”
Section: Interaction Of Rac1 With Tgfβ Signalingmentioning
confidence: 99%
“…Recently, Ungefroren et al have suggested that RAC1b confers anti-oncogenic properties to pancreatic carcinoma cells not only by acting as an antagonist of RAC1, but also by directly affecting the regulation of main components of TGFβ signal pathway [ 176 ]. Ungefroren et al have also recently revealed an unexpected role of RAC1B in the regulation of TGFβ secretion implicated in cell motility suppression [ 158 ]. It is interesting to note that RAC1b increases malignant transformation in response to other EMT-inducers, such as MMP3 [ 177 , 178 ].…”
Section: Actin-related Regulatory Functions That Control Tgfβ Signmentioning
confidence: 99%
“…However, based on our results, a reduction in Smad3 abundance may also remove a barrier to induction of EMT and invasive activities [ 41 ], mediating relief from the tumor-suppressive effects of aTGF-β1 and RAC1b. In addition, we observed that in the same cells, aTGF-β1 promoted proliferation and therefore antagonized the action of exogenous (recombinant human) TGF-β1 on these cells [ 43 ]. Very recent results with cells, in which the endogenous TGFB1 gene had been silenced, indicate that aTGF-β1 can even act an endogenous inhibitor of exogenous, recombinant human (rh)TGF-β1 [ 44 ].…”
Section: Autocrine Tgf-β In the Regulation Of Specific Proteinsmentioning
confidence: 99%